Liderança feminina nas organizações: discursos sobre a trajetória de vida e de carreira de executivas - Medeiros, Adriana Silva (Universidade do Vale do Rio dos Sinos, 2014)
The research sought to understand women’s perception in leadership position about their professional and personal life, especially with regard to perceived social demands, the challenges faced in this journey and coping strategies adopted. For this, there was an eminently qualitative and exploratory study, of cross-sectional nature. The strategy of data collection involved eight narrative interviews, whose analysis focused on individual character, namely, the understanding of the reports concerning the interviewees’ personal and professional experiences about the trajectory to achieve strategic leadership positions in organizations. Data analysis was performed by analysis of discourse, supported by NVivo's data categorization software. The theoretical framework was sustained on four main approaches: a) leadership and how this concept is crossed by the issue of gender, b) the construction of social representations in relation to gender, c) the historical recovery of the trajectory of women in the market work and in management positions and finally, d) the feminine leadership constructed and consolidated within the social context presented and its implications for personal and professional lives of these women. The survey revealed that despite not feeling extreme situations related to discrimination and gender barriers, the demands and the need to prove their competence is remarkable as well as the imperative to sustain systematically their position in a universe that is still predominantly male. With respect to family issues, there are still difficulties in reconciling personal and professional life, because the trajectory required innumerable choicesand sacrifices on behalf of the reach of key positions in organizations. Regarding leadership, it was perceived clearly the intention of empowerment through knowledge as a way to ensure their position and a management practice based on people, sharing and meritocracy.
Keywords: Liderança feminina; Gênero; Demandas sociais; Trabalho; Trajetórias de vida e de carreira; Organizações; Female leadership; Genre; Social demands; Work; Trajectories of life and career; Organizations; ACCNPQ::Ciências Sociais Aplicadas::Administração